Altered T cell receptor beta repertoire patterns in pediatric ulcerative colitis. (27th January 2019) - Werner, L; Nunberg, M Y; Rechavi, E; Lev, A; Braun, T; Haberman, Y; Lahad, A; Shteyer, E; Schvimer, M; Somech, R; Weiss, B; Lee, Y N; et al.
Summary: The antigenic specificity of T cells occurs via generation and rearrangement of different gene segments producing a functional T cell receptor (TCR). High-throughput sequencing (HTS) allows in-depth assessment of TCR repertoire patterns. There are limited data concerning whether TCR repertoires are altered in inflammatory bowel disease. We hypothesized that pediatric ulcerative colitis (UC) patients possess unique TCR repertoires, resulting from clonotypical expansions in the gut. Paired blood and rectal samples were collected from nine newly diagnosed treatment-naive pediatric UC patients and four healthy controls. DNA was isolated to determine the TCR-β repertoire by HTS. Significant clonal expansion was demonstrated in UC patients, with inverse correlation between clinical disease severity and repertoire diversity in the gut. Using different repertoire variables in rectal biopsies, a clear segregation was observed between patients with severe UC, those with mild–moderate disease and healthy controls. Moreover, the overlap between autologous blood–rectal samples in UC patients was significantly higher compared with overlap among controls. Finally, we identified several clonotypes that were shared in either all or the majority of UC patients in the colon. Clonal expansion of TCR-β-expressing T cells among UC patients correlates with disease severity and highlights their involvement in mediating intestinal inflammation. Graphical Abstract: